Network Communities as an Expression of Inclusive Culture of Participation in Political Protests: The Sunflower Movement Case Study - Piechota, Grażyna (Communication Today, 2018)
This article offers an analysis of the ways creation of a community influences the activity of users expressed in their network behaviour. It has been assumed that a varied choice of used tools and channels of communication characterising societies with a high level of technological development simultaneously influences fragmentation of network communication processes. Inclusive culture of participation becomes limited, which is the result of the degree of engagement of users which influence participation in a virtual community. This leads to their differentiation in relation to content and choice of the used channels during network communication. Another factor limiting participation is also communication activity of administrators of a virtual community who impose the dominating content of messages. The research results are a part of scientific research concerning the role of leaders in network communication as well as the creation of network communities that accompany political protests and demonstrations.